Social anxiety in adolescence and the first timing of parental home leaving and living with a partner: a longitudinal population-based Young-HUNT3 study in Norway - Malik Dimbei Halidu; Cathrine Fredriksen Moe; Samira Behboudi-Gandevani; Tommy Haugan (Frontiers in Public Health)
BackgroundSocial anxiety can make significant life transitions from adolescence to young adulthood particularly stressful. Despite the potential impact, few population-based longitudinal studies have examined the relationship between social anxiety and the timing of key markers of the transition to adulthood. This study investigated the association between social anxiety and the timing of two critical life events: first leaving the parental home and first living with a partner.MethodsData were drawn from 8,199 adolescents aged 13–19 who participated in the Young-HUNT3 survey (2006–2008) in Norway, linked with event registration data from Statistics Norway through 2020. Social anxiety was assessed via the Short Form of the Social Phobia and Anxiety Inventory for Children, with scores ranging from 1 to 5. Accelerated failure time (AFT) regression analyses with a Weibull distribution were conducted to evaluate the relationship between social anxiety and the timing of first leaving the parental home and first living with a partner.ResultsThe final analytic sample size was 8,045. The median age for first leaving the parental home was 21, whereas the median age for first starting to live with a partner was 24. Higher levels of social anxiety were modestly associated with delays in both life transitions. Specifically, a one-unit increase in the social anxiety score was associated with an approximate one-month delay in leaving the parental home (T = 1.005; p < 0.05) and a two-month delay in first living with a partner (T = 1.010; p < 0.001). The predicted mean indicates a difference of 4 months for leaving the parental home and 8 months for first living with a partner, comparing adolescents with the lowest (score of 1) to the highest (score of 5) within the social anxiety spectrum.ConclusionThis study highlights the association between social anxiety and delays in key life transitions from adolescence to early adulthood. Despite these delays, socially anxious adolescents in Norway appear to reach these milestones—leaving the parental home and living with a partner—in their early twenties, similar to their peers. Although the findings are modest, practically, this information may still hold significant value in informing care providers and policymakers to focus on adolescents as a potential period for implementing evidence-based programs aimed at social anxiety. Future research should explore other stress-inducing life events and examine the long-term socioeconomic and health outcomes of adolescents with social anxiety.